Pengaruh Komposisi 2,4-D dan BAP Terhadap Pembentukan Kalus Eksplan Pucuk Nilam (Pogostemon Cablin Benth.) secara In Vitro dengan Pemotongan Horizontal dan Vertikal - Khairan Khairan; Betty Mauliya Bustam; Yunita; Riska Meilinda; Raudhatul Muna (Biotropic : The Journal of Tropical Biology, 2021)
This study aims to determine the effect of 2,4-Diclorophenoxy Acetic Acid (2,4-D) and Benzyl Amino Purin (BAP) on the formation of callus of patchouli (Pogostemon cablin Benth.) shoot explants by horizontal and vertical cutting methods. The parameters that observed in this study were the percentage growth of callus, time appearance of callus, weight of callus and the morphology of callus. The results showed that horizontal cutting method was able to induce callus growth with the percentages growth of callus were 18,75%, with the time appearance of callus was at 16 days at P1; P10; P12; P13 dan P14. The highest weight of callus obtained was 0.19 grams at P8. The results also showed that the callus yielded had a yellow and cream color, with a compact and crumb textures. Meanwhile, the vertical cutting method was able to induce callus formation with the percentage growth of callus were 12,5%. The fastest time of callus appearance was obtained in P6 and P8, which was 12 day after planting with the highest weight of callus obtained was 0.05 grams at P12. The results also showed that vertical cutting method had brown and dark-brown of callus with a compact and crumb textures.